2013
DOI: 10.1042/bsr20120123
|View full text |Cite
|
Sign up to set email alerts
|

ALG-2-interacting Tubby-like protein superfamily member PLSCR3 is secreted by an exosomal pathway and taken up by recipient cultured cells

Abstract: PLSCRs (phospholipid scramblases) are palmitoylated membrane-associating proteins. Regardless of the given names, their physiological functions are not clear and thought to be unrelated to phospholipid scrambling activities observed in vitro. Using a previously established cell line of HEK-293 (human embryonic kidney-293) cells constitutively expressing human Scr3 (PLSCR3) that interacts with ALG-2 (apoptosis-linked gene 2) Ca2+-dependently, we found that Scr3 was secreted into the culture medium. Secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…As shown in Figure 1 , intensity of the WB signal of Scr3 in the TCL was slightly stronger in 3T3 cells than in 3T3-L1 cells under both subconfluent ( sub ) and confluent ( con ) conditions despite weaker or similar signal intensities of the two loading controls used ( flotillin-2 and GAPDH ). We previously found that Scr3, either exogenously expressed in human embryonic kidney (HEK)293 cells or endogenously expressed in human bladder carcinoma T-24 cells, was consistently secreted into the culture medium in the form of extracellular microvesicles (exosomes) [ 18 ]. Likewise, secretion of Scr3 as the form of exosomes was also observed in mouse 3T3 and 3T3-L1 cells ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 1 , intensity of the WB signal of Scr3 in the TCL was slightly stronger in 3T3 cells than in 3T3-L1 cells under both subconfluent ( sub ) and confluent ( con ) conditions despite weaker or similar signal intensities of the two loading controls used ( flotillin-2 and GAPDH ). We previously found that Scr3, either exogenously expressed in human embryonic kidney (HEK)293 cells or endogenously expressed in human bladder carcinoma T-24 cells, was consistently secreted into the culture medium in the form of extracellular microvesicles (exosomes) [ 18 ]. Likewise, secretion of Scr3 as the form of exosomes was also observed in mouse 3T3 and 3T3-L1 cells ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Decrease in Scr3 in the protein level (to 13.9–22.6%) more than in the mRNA level (to 33.2–54.0%) during adipocyte differentiation is partly explained by enhanced secretion of Scr3 in the form of extracellular microvesicles named exosomes ( Figures 1 – 3 and Supplementary Figure S2). We previously reported that exosomal secretion of exogenously expressed Scr3 was significantly reduced and that subcellular localization was changed from the cytoplasmic puncta to nucleus by inhibition of palmitoylation of Scr3 by 2-bromopalmitate in HEK293 cells [ 18 ]. Since 2-bromopalmitate was toxic to 3T3-L1 cells when the cells were cultured for a long time, we could not investigate the effects of inhibition of palmitoylation of Scr3 on adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is important to point out the different cell types under investigation, neurons in the Rami study and endothelial cells in ours, both suggest an increase in PLSCR1 shortly after reperfusion is established. As for the decrease in PLSCR1 protein during the hypoxic period that we observed, the potential for PLSCR1 to be released from the cell membrane must be considered and may be due to shedding of the protein into the culture media as was recently described for PLSCR3 [146]. …”
Section: The Response Of Phospholipid Scramblase 1 To Hypoxiamentioning
confidence: 96%
“…For example, mutagenesis of the cysteine residues of PLSCR3 critical for its palmitoylation led to its redistribution to the nuclear compartment [85]. Furthermore, secretion of PLSCR3 in exosomes was inhibited by 2-bromopalmitate [86]. NLS signals are also found in PLSCR2, PLSCR3, and PLSCR4.…”
Section: Plscr Familymentioning
confidence: 99%